Laparoscopic gastrectomy vs open gastrectomy with D2 lymph node dissection in gastric cancer: Early postoperative outcomes and feasibility of laparoscopic procedures - Lale, Azmi; Aygen, Erhan (My University, 2021)
Introduction: Minimal invasive gastrectomy procedures offer better postoperative recovery and lower com plication rates. Furthermore, oncological outcomes are not inferior to conventional open gastrectomy (OG)procedures. The aim of this study was to evaluate the short-term postoperative clinical outcomes and his topathological results after laparoscopic gastrectomy (LG) versus OG in our clinic. Materials and Methods: A total of 50 eligible patients were included in the study. All the patients were dividedinto two main groups as LG (n=18) and OG (n=32). Demographic parameters, intraoperative findings, earlypostoperative outcomes, and histopathological findings were compared between the groups. Results: Age, gender, BMI, comorbid diseases, ASA scores, neoadjuvant treatment history were similar inboth LG and OG groups. The mean first flatus time (LG: 2.01 vs. OG: 2.62 days, p=0.002) and hospital stay(LG: 10.2 vs. OG: 14.4 days, p=0.004) were shorter and estimated blood loss was lesser (LG: 147.5 vs. OG:194.5 ml, p=0.041) in LG patients. The duration of operation significantly higher in LG patients (285.7 vs.239.7 min, p<0.001). Postoperative 30-day minor and major complications and mortality rates were lesserin LG patients but the differences were not significant. The mean number of retrieved total lymph nodes intotal gastrectomy patients (LTG: 39.2 vs. OTG: 38.7, p=0.982) and in distal gastrectomy patients (LDG: 32.4vs. ODG: 37.1, p=0.649) were similar to open procedures. Conclusion: LG procedures are superior to OG with advantageous postoperative clinical outcomes and sim ilar pathologic results in both distal or total gastrectomy patients and can be safely performed for early orlocally advanced gastric carcinomas.
Keywords: Onkoloji; Cerrahi